1989
DOI: 10.1128/mcb.9.6.2396
|View full text |Cite
|
Sign up to set email alerts
|

The upstream muscle-specific enhancer of the rat muscle creatine kinase gene is composed of multiple elements.

Abstract: A series of constructs that links the rat muscle creatine kinase promoter to the bacterial chloramphenicol acetyltransferase gene was generated. These constructs were introduced into differentiating mouse C2C12 myogenic cells to localize sequences that are important for up-regulation of the creatine kinase gene during myogenic differentiation. A muscle-specific enhancer element responsible for induction of chloramphenicol acetyltransferase expression during myogenesis was localized to a 159-base-pair region fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 48 publications
2
97
0
Order By: Relevance
“…In addition, there was diminished DNA binding activity of the muscle-specific transcription factor MEF-2. These data and other experimental evidence indicate that MEF-2 is involved in the activation of muscle-specific genes, including rat myosin light chain 2 slow, human myoglobin, rat muscle creatine kinase, mouse troponin C slow, and human beta enolase (14,15,20,26,50). In addition, MEF-2 has been proposed to serve as a nodal point in the mechanisms by which motor nerves control the program of gene expression in skeletal muscle fibers and in the pathway leading to cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, there was diminished DNA binding activity of the muscle-specific transcription factor MEF-2. These data and other experimental evidence indicate that MEF-2 is involved in the activation of muscle-specific genes, including rat myosin light chain 2 slow, human myoglobin, rat muscle creatine kinase, mouse troponin C slow, and human beta enolase (14,15,20,26,50). In addition, MEF-2 has been proposed to serve as a nodal point in the mechanisms by which motor nerves control the program of gene expression in skeletal muscle fibers and in the pathway leading to cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the combination of the MCK enhancer and the 1-kb region produces greater activity in both thigh and cardiac muscle than does either region alone (16). To further delineate the active portions of the 1-kb region, we compared mouse, rat, rabbit, and human MCK sequences (27,31,65,73) to determine which portions were most highly conserved. The first 358 bp of the 5Ј region exhibited more than 50% sequence similarity, whereas there was little similarity between bp Ϫ1049 and Ϫ359.…”
Section: Resultsmentioning
confidence: 99%
“…The 5Ј MCK enhancer contains a number of sequence motifs-including the E box, CArG, and AT-rich sites-which are recognized by tissue-specific and ubiquitous transcription factors. Mutational analysis of these sites showed that several are critical for activity in cultured skeletal and cardiac muscle (1,7,21,27); however, the mutations had different effects when tested in transgenic mice (16). Mutation of the Right E box, which is a target for basic-helix-loop-helix (bHLH) DNA-binding factors (17,48,69) such as the myogenic factors MyoD and myogenin and the ubiquitous bHLH factors E12/E47 and E2-2 (2,40,45), caused a nearly 100-fold reduction in expression in transfected skeletal muscle cells and a 6-fold decrease in expression in transiently transfected cardiomyocytes (1,7).…”
mentioning
confidence: 99%
“…These binding sites contribute to the in vivo activity of the MCK (Gossett et al 1989;Horlick and Benfield 1989) and m y o s i n light-chain 1/3 (Donoghue et al 1988;Wentworth et al 1991) gene enhancers, and the myosin light-chain type 2A (Braun et al 1989;Zhu et al 1991) and creatine kinase B (Hobson et al 1988 promoters. These sites have been shown 2C) were inserted into pBLCAT2, and the resulting plasmids were transfected into NIH-3T3 cells.…”
Section: Potential Target Promoters For Rsrf Proteinsmentioning
confidence: 99%
“…One, from the promoter of the cellular immediate early gene N10 (Hazel et al 1988;Changelian et al 1989;Ryseck et al 1989), represents an example of the most common sequence recovered in the site selection CTATT-TATAG. The second, from the muscle-specific creatine kinase (MCK) gene enhancer, represents a variant site, CTAAAAATAA, identified previously as a functional element and factor-binding site in this enhancer (Gossett et al 1989;Horlick and Benfield 1989;Mueller and Wold 1989;Horlick et al 1990). …”
Section: Interaction Of Rsrfc4 With Natural Cta(t/a)4tag Elementsmentioning
confidence: 99%